A DT-diaphorase responsive theranostic prodrug for diagnosis, drug release monitoring and therapy1. Issue 46 (11th June 2015) - Liu, Peilian; Xu, Jiangsheng; Yan, Donghang; Zhang, Peisheng; Zeng, Fang; Li, Bowen; Wu, Shuizhu
<x xml:space="preserve">Abstract</x> A DT-diaphorase responsive theranostic prodrug has been developed for diagnosis, tracking of drug release and selectively killing cancer cells over-expressed with DT-diaphorase.